2015
DOI: 10.4103/0189-6725.172574
|View full text |Cite
|
Sign up to set email alerts
|

Primary congenital bladder diverticula: Where does the ureter drain?

Abstract: Background:Primary congenital bladder diverticulum (PCBD) is related to a deficient detrusor layer allowing out-pouching of the bladder mucosa through the inadequate muscularis wall. We aimed to review our experience with symptomatic PCBD in order to correlate clinical findings with anatomical aspects and to present late outcome.Materials and Methods:We reviewed all patients operated in our institution since 2004. We evaluated the charts for complaints, radiological exams, method of treatment, complications an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Studies which included patients above 18 years of age, reported UR due to other etiologies, or their full text was not accessible, were excluded. With regards to bladder diverticula causing UR, 20 articles, including 49 cases, were found, while only four articles, including five cases, were found for MDC 8–31 . Besides, no report for UR due to ureteral stump syndrome was found with the mentioned keywords.…”
Section: Discussionmentioning
confidence: 99%
“…Studies which included patients above 18 years of age, reported UR due to other etiologies, or their full text was not accessible, were excluded. With regards to bladder diverticula causing UR, 20 articles, including 49 cases, were found, while only four articles, including five cases, were found for MDC 8–31 . Besides, no report for UR due to ureteral stump syndrome was found with the mentioned keywords.…”
Section: Discussionmentioning
confidence: 99%